Impacts of lung cancer multidisciplinary meeting presentation: Drivers and outcomes from a population registry retrospective cohort study. (January 2022) - Lin, Tiffany; Pham, Jonathan; Paul, Eldho; Conron, Matthew; Wright, Gavin; Ball, David; Mitchell, Paul; Atkin, Nicola; Brand, Margaret; Zalcberg, John; Stirling, Robert G.
Highlights: In this paper, we reviewed 9, 628 lung cancer cases diagnosed between 2011 and 2020 to assess. Impacts of multidisciplinary meeting (MDM or tumour board) presentation. Patients of male sex, >80 years of age, of worse performance status, advanced clinical stage and poor clinical characterisation were less likely to be presented at MDM. Patients discussed at MDM had a 25% lower risk of mortality compared to those not discussed. The protective effect of MDM presentation was preserved across all hospital types and locations. Abstract: Introduction: Multidisciplinary Meetings (MDM) are recommended in routine lung cancer care, however its broader impacts demand further evaluation. We assessed the drivers and impacts of MDM presentation in the Victorian Lung Cancer Registry (VLCR). Methods: We examined the effect of MDM presentation on receipt of treatment and survival in VLCR patients diagnosed between 2011 and 2020. We compared patient characteristics, drivers of MDM discussion and survival between the two groups. Results: Of 9, 628 patients, 5, 900 (61.3%) were discussed at MDM, 3, 728 (38.7%) were not. In the non-MDM group, a lower proportion received surgery (22.1% vs. 31.2%), radiotherapy (34.2% vs. 44.4%) and chemotherapy (44.7% vs. 49.0%). Patients were less likely to be discussed if ≥80 years (OR 0.73, p < 0.001), of ECOG performance status (PS) 4 (OR 0.23, p < 0.001), clinical stage IV (OR 0.34, p < 0.001) or referred from regional (OR 0.52, p < 0.001) or private hospital (OR 0.18, p < 0.001). MDM-presented patients had better median survival (1.70 vs 0.75 years, p < 0.001) and lower adjusted mortality risk (HR 0.75; 0.71–0.80, p < 0.001), a protective effect consistent across all hospital types. Undocumented PS, histopathology and clinical stage were associated with lower likelihood of MDM discussion and worse mortality. Conclusions: In the VLCR, being male, ≥80 years, of poorer PS, advanced clinical stage and poor clinical characterisation significantly disadvantaged patients in relation to MDM discussion. MDM-discussed patients were more likely to undergo treatment and had a 25% lower risk of mortality. This study supports the use of MDMs in lung cancer and identifies areas of inequity to be addressed.